PEMBENTUKAN KATA DALAM BAHASA: KAJIAN KONSEPTUAL TENTANG MORFOLOGI (Word Formation in Language: A Conceptual Study of Morphology) - Anggia Putri; Lilis Karolina Perangin-angin; Sophie Yuninda Saputri; Salsa Billa Atmadja; Nadea Br Pinem (Journal Education and Government Wiyata, 2025)
This research aims to examine basic concepts in morphology, especially those related to word formation in language. The main focus of this article is to understand how various morphological processes, such as derivation, affixation, composition, and reduplication, play a role in word formation in human languages. The method used in this research is a conceptual approach and theoretical analysis, by reviewing existing literature regarding morphological theories from a structuralist and generative perspective. The discussion includes an analysis of the different types of morphemes, morphological processes that change the form and meaning of words, as well as the relationship between morphology and semantics in word formation. The research results show that word formation in a language does not only depend on morphological structure, but is also influenced by the semantic and syntactic context in the language. In addition, the generative approach offers a more flexible view in understanding the dynamics of word formation, while the structuralist approach places more emphasis on the analysis of morphemes and affixes in a particular language context. This article also discusses the conceptual implications of morphological studies in the field of applied linguistics, such as language teaching and translation, as well as the importance of understanding morphology in the development of linguistic technology.